Incidence and predictors of pulmonary aspergillosis in patients with lung cancer: a systematic review and meta-analysis - Teng, Geling; Jin, Feng; Zhang, Hua; Zhang, Min (Frontiers in Medicine, 2025)
BackgroundPulmonary aspergillosis is a rare but serious complication following lung cancer surgery, increasing the risk of mortality. The incidence of pulmonary aspergillosis and its risk factors among lung cancer patients is unknown. This study systematically investigates the incidence and associated risk factors of pulmonary aspergillosis in lung cancer patients.MethodsThe databases PubMed, Web of Science, Scopus, Embase, CINAHL, and the Cochrane Library were comprehensively searched from their inception to March 2025. The overall incidence of pulmonary aspergillosis among lung cancer patients was analyzed using a random-effects model with logit transformation. Risk factors for pulmonary aspergillosis in lung cancer patients were presented as odds ratios (ORs) with 95% confidence intervals (CIs), calculated using a random-effects model.ResultsNine retrospective studies involving 20,138 patients with lung cancer were selected for the final analysis. The overall incidence of pulmonary aspergillosis in lung cancer patients was 2.4% (95% confidence interval [CI]: 1.5–3.2%). Subgroup analyses revealed higher incidences of pulmonary aspergillosis than corresponding subgroups in the following categories: Asia (2.8%; 95% CI: 2.0–3.7%), diagnosis by serological test (11.7%; 95% CI: 8.0–15.4%), patients with both non-small cell lung cancer and small cell lung cancers (3.6%; 95% CI: 2.0–5.2%), patients treated with chemoradiotherapy (5.7%; 95% CI: 1.6–9.7%), and pooled studies with moderate quality (2.9%; 95% CI: 1.7–3.2%). Moreover, the risk factors for pulmonary aspergillosis in lung cancer patients included male sex (OR: 1.96; p = 0.008), current or past smoking (odds ratio [OR]: 2.92; p < 0.001), chronic obstructive pulmonary disease (OR: 1.88; p = 0.011), interstitial lung disease (OR: 3.71; p < 0.001), pulmonary tuberculosis (OR: 2.79; p = 0.028), and treatment with double lobectomy (OR: 2.74; p < 0.001).ConclusionOur study highlights pulmonary aspergillosis as a significant complication in lung cancer patients, with an overall incidence of 2.4%. The identified risk factors provide crucial insights for targeted screening and intervention in this patient population. Future research should focus on validating these findings in prospective studies and exploring the underlying biological mechanisms to develop more effective preventive and treatment strategies.Systematic review registrationThis study was registered in the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY) platform (number: INPLASY2024100066).